The Role of Local Wisdom in Reducing Toddler Morbidity and Mortality Rates Through Health Promotion Strategies - Joaquim Pinto; Acacio de Jesus; Herminio Noronha; Ostelino da Silva Belo; Manuel Francisco da Costa (Medical Studies and Health Journal (SEHAT), 2024)
This research explores the role of local wisdom in reducing morbidity and mortality among children under five through health promotion strategies using a systematic literature review approach. Local wisdom, which includes knowledge, practices and traditions passed down from generation to generation, has been proven to have a significant contribution in increasing the effectiveness of health interventions by adapting health programs to the community's cultural context. This study analyzes how local wisdom is applied in various health promotion strategies, including community empowerment, social support, and advocacy. The findings show that the integration of local wisdom in health programs can increase community acceptance and participation, and has the potential to reduce infant mortality and morbidity rates. However, this study also identified limitations in the existing literature, including variability in study quality and data limitations. Recommendations for policy and practice include developing local wisdom-based programs, training health workers, partnerships with community leaders, and ongoing evaluation. This research makes an important contribution to understanding how local wisdom-based approaches can be integrated to achieve better health outcomes.